CLINICAL FORMS OF CHRONIC SUPPURATIVE OTITIS MEDIA AND THEIR PREVALENCE AMONG PATIENTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Chronic suppurative otitis media (CSOM) is a purulent inflammatory disease of the tympanic cavity and is clinically divided into several forms: mesotympanitis, epimesotympanitis, and epitympanitis. Each form differs in its anatomical localization, clinical manifestations, risk of complications, and therapeutic approaches.